2016
DOI: 10.1002/wrna.1342
|View full text |Cite
|
Sign up to set email alerts
|

A structurally plastic ribonucleoprotein complex mediates post‐transcriptional gene regulation in HIV‐1

Abstract: HIV replication requires the nuclear export of essential, intron-containing viral RNAs. To facilitate export, HIV encodes the viral accessory protein Rev which binds unspliced and partially spliced viral RNAs and creates a ribonucleoprotein complex that recruits the cellular Chromosome maintenance factor 1 export machinery. Exporting RNAs in this manner bypasses the necessity for complete splicing as a prerequisite for mRNA export, and allows intron-containing RNAs to reach the cytoplasm intact for translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 120 publications
(192 reference statements)
0
19
0
1
Order By: Relevance
“…However, the virus has found many solutions to maximize the information contained in its genome, such as using an adaptable Rev monomer to assemble a higher order oligomeric RNA export complex59. We believe that the post-translational ubiquitination of Tat represents another viral strategy of genetic multi-tasking.…”
Section: Discussionmentioning
confidence: 99%
“…However, the virus has found many solutions to maximize the information contained in its genome, such as using an adaptable Rev monomer to assemble a higher order oligomeric RNA export complex59. We believe that the post-translational ubiquitination of Tat represents another viral strategy of genetic multi-tasking.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxed‐specificity ARMs and RNAs have been found that transit recognition strategies between distinct lentiviral Tat‐TAR interactions and between distinct lambdoid N‐boxB interactions . Like Rev‐RRE, Tat‐TAR and N‐boxB interactions are characterized by disordered proteins binding RNAs sites with conformational flexibility, a feature of RNA‐protein interactions relating to their role in complex, fine‐tuned regulation …”
Section: Discussionmentioning
confidence: 91%
“…HIV Rev is a small, 114 amino acid, essential regulatory protein that mediates the nuclear export of incompletely spliced viral transcripts that contain a large, structured RNA, the Rev‐response element (RRE) . Rev initially binds to a high‐affinity site in RRE region IIB (IIB) via its ARM that comprises residues 34 to 50, and then Rev binds to secondary sites with multimerization and further conformational changes followed by recruitment of host factors that mediate export …”
Section: Introductionmentioning
confidence: 99%
“…Complex retroviruses such as human immunodeficiency virus (HIV) and human T-cell lymphotropic virus (HTLV) were initially shown to encode regulatory proteins (Rev and Rex) that facilitate this process by binding to cis -acting elements in the viral mRNAs that retain introns (for reviews, see Pollard and Malim, 1998; Shida, 2012; Fernandes et al ., 2016). Rev and Rex then recruit chromosome region maintenance 1/exportin 1, a cellular export receptor, enabling nucleocytoplasmic export (Fornerod et al ., 1997; Booth et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%